Presenting a Social Capital Management Model in the General Directorate of Education in Kermanshah Province with a Grounded Theory Approach (Case Study: Primary School Principals) - Moftoon, Farzaneh; Malekian, Faramarz; Islampanah, Maryam; Karam Afrooz, Javad (Iranian Journal of Educational Sociology, 2022)
Purpose: Social capital plays an important role in the success of any organization, including the education organization. As a result, the purpose of this study was presenting a social capital management model in the general directorate of education in Kermanshah province with a grounded theory approach.Methodology: This research in terms of purpose was applied and in terms of implementation method was mixed (qualitative and quantitative). The research population in the qualitative part was experts and senior managers of education in Kermanshah province and in the quantitative part were the principals of primary schools in Kermanshah province. The sample size in the qualitative part was estimated according to the principle of theoretical saturation 11 people who were selected by purposive sampling method and in the quantitative part was estimated according to Krejcie and Morgan table 332 people who were selected by random cluster sampling method. The research instrument in the qualitative part was a semi-structured interview and in the quantitative part was a researcher-made questionnaire, whose psychometric indices was confirmed and for data analysis was used from the methods of coding in MAXQDA software and exploratory factor analysis in LISREL software.Findings: Findings showed that in the central category of social capital management in education, causal conditions including categories of organizational factors, social factors and individual factors, contextual conditions including categories of social bonds of employees, cultural and social commitments and sustainable social development, intervening conditions including categories of legal requirements and frameworks, civic participation networks, organizational policies and organizational culture, strategies including categories of knowledge management, organizational resilience, job turnover and organizational participation and outcomes including categories of organizational outcomes, individual outcomes and social outcomes. Other findings showed that the factor load of all sub-categories except sense of identity on causal conditions, all sub-categories except collective power on contextual conditions, all sub-categories except success and education on intervening conditions, all sub-categories on strategies and all sub-categories except human capital accumulation, social cohesion, organizational learning, organizational entrepreneurship and interpersonal trust on outcomes were confirmed.Conclusion: Regarded to the importance of identified categories and concepts for the social capital management in education, planning is essential to improve the categories through their concepts.